Novel Tubular Carbon Membranes Prepared from Natural Rattans - Xuezhong He (C, 2019)
The novel tubular carbon membranes produced from natural materials are, for the first time, reported. The novelty of this idea is to use natural rattans as precursors for making carbon membranes to address the challenges of cellulose polymers. The rattan precursors were carbonized to present evenly distributed channels inside the tubular carbon membranes. Each channel has an inner diameter of 2 × 10−4 m with a dense-selective inner layer and a porous outer layer. Future work on selection of suitable rattans, proper pre-treatment, carbon structure tailoring can be conducted to open a new research field of carbon membranes/materials.